The impact of green monetary policy on sustainable economic development in pioneer countries - Chi, Vu Mai; Anh, Nguyen Tuan; Huyen, Nguyen Thi Thu (Asian Economic and Financial Review, 2025)
Climate change is currently one of the greatest challenges facing humanity, significantly impacting the effectiveness of economic policies. To address this issue, green monetary policy has been proposed as a strengthened measure that not only stabilizes prices and promotes economic growth but also helps reduce negative environmental impacts and supports the transition to a low-emission economy. Our paper aims to assess the impact of green monetary policy in pioneering countries, thereby making recommendations for expanding and perfecting this policy on a global scale. The paper focuses on studying the impact of green monetary policy in pioneering countries, including the United Kingdom, Germany, and China, during a period of intense global economic fluctuations from 2000 to 2020. The paper uses a PVAR model to analyze the impact of green monetary policy through variables such as interest rates, special reserves, inflation, unemployment rates, carbon emissions, and economic growth. Model results and some tests indicate that green monetary policy has a positive impact on long-term economic growth while helping to reduce carbon emissions in the environment. Every country should implement monetary policy in a green direction to contribute to economic and environmental stability. In this analysis, the authors provide recommendations to promote the greening of monetary policies in other countries worldwide.